2013
DOI: 10.5146/tjpath.2015.01338
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of mast cell count in oral reactive lesions and its association with inflammation

Abstract: Objective: Reactive hyperplastic lesions are one of the most common lesions of the oral cavity. Mast cells can be found in various oral lesions. however, the exact role of mast cells in oral reactive lesions is not fully understood. The aim of this study was to compare the mast cells count in various oral reactive lesions and to evaluate the correlation between the mast cells number and the intensity of inflammation. Material and Method:This cross-sectional study was performed on 80 samples of oral reactive le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Chymase and tryptase from mast cells facilitate fibroblast proliferation and type I collagen synthesis. [ 24 ] According to our findings, the severity of inflammation was high in pyogenic granulomas, followed by inflammatory fibrous hyperplasia and irritation fibroma. Hunasgi et al .…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Chymase and tryptase from mast cells facilitate fibroblast proliferation and type I collagen synthesis. [ 24 ] According to our findings, the severity of inflammation was high in pyogenic granulomas, followed by inflammatory fibrous hyperplasia and irritation fibroma. Hunasgi et al .…”
Section: Discussionmentioning
confidence: 59%
“…The fibrotic events may be attributed to the functional fibroblasts activation by fibrogenic cytokines such as tumour necrosis factor, platelet-derived growth factor, and basic fibroblast growth factor. [ 24 30 ] Epithelial thickness was increased in inflammatory fibrous hyperplasia compared to other lesions. This may be due to the cytokines released by the inflammatory cells, resulting in the acanthosis and pseudoepitheliomatous hyperplasia of the overlying epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…The low recurrence rate of PGCG might be partly explained by low capacity in neovascularization of granulation tissue. Another reason was that the mast cell count of PGCG was the lowest among all types of epulis [ 10 , 31 ], while the mast cells were important sources of some proangiogenic and angiogenic factors [ 32 ]. Striking difference was reported in the results by Babu and Savage [ 7 , 13 ], which demonstrated that PGCG had the highest recurrence rate among all types of epulis because the cells of PGCG show high proliferative potential.…”
Section: Discussionmentioning
confidence: 99%
“…Soft-tissue neoplasms, like neurilemoma [8,10] neurofibroma, lipoma [8,14] neoplasms of minor salivary glands, may also be considered for the differential diagnosis [18], in addition to inflammatory and reactive lesions [8][9][10].…”
Section: Discussionmentioning
confidence: 99%